Y-Chromosome Evidence for Differing Ancient Demographic Histories in the Americas (2003)
ABSTRACT: To scrutinize the male ancestry of extant Native American populations, we examined eight biallelic and six microsatellite polymorphisms from the nonrecombining portion of the Y chromosome, in 438 individuals from 24 Native American populations (1 Na Dene´ and 23 South Amerinds) and in 404 Mongolians. One of the biallelic markers typed is a recently identified mutation (M242) characterizing a novel founder Native American haplogroup. The distribution, relatedness, and diversity of Y lineages in Native Americans indicate a differentiated male ancestry for populations from North and South America, strongly supporting a diverse demographic history for populations from these areas. These data are consistent with the occurrence of two major male migrations from southern/ central Siberia to the Americas (with the second migration being restricted to North America) and a shared ancestry in central Asia for some of the initial migrants to Europe and the Americas. The microsatellite diversity and distribution of a Y lineage specific to South America (Q-M19) indicates that certain Amerind populations have been isolated since the initial colonization of the region, suggesting an early onset for tribalization of Native Americans. Age estimates based on Y-chromosome microsatellite diversity place the initial settlement of the American continent at ∼14,000 years ago, in relative agreement with the age of well-established archaeological evidence.